High-density lipoprotein cholesterol as a predictor of clinical outcomes in patients achieving low-density lipoprotein cholesterol targets with statins after percutaneous coronary intervention. Issue 23 (10th June 2011) - Seo, Suk Min; Choo, Eun-Ho; Koh, Yoon-Seok; Park, Mahn Won; Shin, Dong Il; Choi, Yoon Seok; Park, Hun-Jun; Kim, Dong Bin; Her, Sung Ho; Lee, Jong Min; Park, Chul Soo; Kim, Pum-Joon; et al.
Abstract : Background: A low level of high-density lipoprotein cholesterol (HDL-C) is strongly associated with cardiovascular events. However, the significance of HDL-C after statin therapy on the outcome of patients who have undergone percutaneous coronary intervention (PCI) with drug eluting stents (DES) is unclear. Objectives: To investigate the significance of HDL-C after statin therapy on cardiovascular events in patients with coronary artery disease after DES implantation. Methods: Patients who underwent PCI with DES from January 2004 to December 2009 were prospectively enrolled. The follow-up lipid panel of 2693 patients (median lab follow-up duration 225 days) who had continued using statins after PCI and who attained low-density lipoprotein cholesterol (LDL-C) <100 mg/dl was analysed. Major adverse cardiac events (MACE), including all-cause death, non-fatal myocardial infarction, and target vessel revascularisation according to follow-up HDL-C level (40 mg/dl for men or 50 mg/dl for women) were compared with the use of propensity scores matching. Results: Median follow-up duration was 832 days. 1585 (58.9%) patients had low follow-up HDL-C and 1108 had high follow-up HDL-C. The low follow-up HDL-C group had significantly higher rates of MACE. Low follow-up HDL-C was a significant independent predictor of MACE (adjusted HR 1.404, 95% CI 1.111 to 1.774, p=0.004). In further analysis with propensity scores matching, overall findings were consistent. Conclusions: Raising HDL-C levels may be a subsequent goal after achieving target LDL-C levels in patients with DES implantation.